2021
DOI: 10.1111/bjso.12505
|View full text |Cite
|
Sign up to set email alerts
|

When and why does political trust predict well‐being in authoritarian contexts? Examining the role of political efficacy and collective action among opposition voters

Abstract: Previous research indicates that trust in the political system increases well-being. Drawing from prior collective action research, we posit that a) the relationship between political trust and well-being would be mediated by collective action partici-K E Y W O R D S collective action, political efficacy, political trust, Turkey, well-being | 863 DOES POLITICAL TRUST SHAPE WELL-BEING? action participation and (3) political efficacy moderates the indirect effect of political trust on wellbeing through collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Nevertheless, positive emotions as antecedents to collective action have received little research attention in the context of Turkey. Of the little work in this area in Turkey, positive emotions derived from being a participant of Turkey's system (e.g., Solak, 2015), and institutional trust and satisfaction with how the democracy works (e.g., Acar & Uluğ, 2021a;Kentmen-Çin, 2015) were negatively related to willingness to participate in system-challenging collective actions.…”
Section: Collective Action and Social Change In Turkey 10mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, positive emotions as antecedents to collective action have received little research attention in the context of Turkey. Of the little work in this area in Turkey, positive emotions derived from being a participant of Turkey's system (e.g., Solak, 2015), and institutional trust and satisfaction with how the democracy works (e.g., Acar & Uluğ, 2021a;Kentmen-Çin, 2015) were negatively related to willingness to participate in system-challenging collective actions.…”
Section: Collective Action and Social Change In Turkey 10mentioning
confidence: 99%
“…Moreover, collective efficacy itself is not monothetic. Thus, heterogeneity for the effect of efficacy on collective action also emerged when researchers considered different types of efficacy (see Acar & Uluğ, 2021a;Hornsey et al, 2006). In a recent study, Cichocka et al (2018), for example, demonstrated that external political efficacy (i.e., perceptions that the government considers one's demands) was negatively related to collective action intentions.…”
Section: Collective Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be high or low. Higher levels of efficacy indicate that citizens believe their government is doing what is best for them and that their actions can positively impact the government (Acar & Ulug, 2021;Schulz, 2005). Meanwhile, low levels of efficacy point toward citizens' lack of faith in their government and the feeling that their actions have little or no impact upon the actions of the government (Pedraza, 2016).…”
Section: Political Efficacymentioning
confidence: 99%
“…A spate of very recent studies has explored support for collective action in Turkey (Acar & Uluğ, 2022; Çakal et al., 2016; Uluğ et al., 2020), some in relation to the Gezi Park protests of 2013 (Ayanian et al., 2021; Baysu & Phalet, 2017; Odağ et al., 2016; Uluğ & Acar, 2019; Uysal & Akfırat, 2021, 2022). For the most part, these studies focused on variables such as anger at perceived injustice, ingroup identification, and beliefs about group efficacy, which are central to the Social Identity Model of Collective Action (SIMCA; see Van Zomeren et al., 2008).…”
Section: Introductionmentioning
confidence: 99%